BMAL1 Regulates the Daily Timing of Colitis - Taleb, Zainab; Carmona-Alcocer, Vania; Stokes, Kyle; Haireek, Marta; Wang, Huaqing; Collins, Stephen M.; Khan, Waliul I.; Karpowicz, Phillip (Frontiers in Cellular and Infection Microbiology, 2022)
Many physiological functions exhibit circadian rhythms: oscillations in biological processes that occur in a 24-hour period. These daily rhythms are maintained through a highly conserved molecular pacemaker known as the circadian clock. Circadian disruption has been proposed to cause increased risk of Inflammatory Bowel Disease (IBD) but the underlying mechanisms remain unclear. Patients with IBD experience chronic inflammation and impaired regeneration of intestinal epithelial cells. Previous animal-based studies have revealed that colitis models of IBD are more severe in mice without a circadian clock but the timing of colitis, and whether its inflammatory and regenerative processes have daily rhythms, remains poorly characterized. We tested circadian disruption using Bmal1-/- mutant mice that have a non-functional circadian clock and thus no circadian rhythms. Dextran Sulfate Sodium (DSS) was used to induce colitis. The disease activity of colitis was found to exhibit time-dependent variation in Bmal1+/+ control mice but is constant and elevated in Bmal1-/- mutants, who exhibit poor recovery. Histological analyses indicate worsened colitis severity in Bmal1-/- mutant colon, and colon infiltration of immune system cells shows a daily rhythm that is lost in the Bmal1-/- mutant. Similarly, epithelial proliferation in the colon has a daily rhythm in Bmal1+/+ controls but not in Bmal1-/- mutants. Our results support a critical role of a functional circadian clock in the colon which drives 24-hour rhythms in inflammation and healing, and whose disruption impairs colitis recovery. This indicates that weakening circadian rhythms not only worsens colitis, but delays healing and should be taken into account in the management of IBD. Recognition of this is important in the management of IBD patients required to do shift work.